2017
DOI: 10.1002/anie.201701523
|View full text |Cite
|
Sign up to set email alerts
|

Domino N‐/C‐Arylation via In Situ Generation of a Directing Group: Atom‐Efficient Arylation Using Diaryliodonium Salts

Abstract: Both aryl components of diaryliodonium salts can be used in a domino one-pot reaction via in situ generation of a directing group. A number of heterocycles undergo N-arylation which is followed by ruthenium-catalyzed C-arylation. Notably the reaction extends well to unsymmetrical diaryliodonium salts with a number of highly selective examples shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 46 publications
2
49
0
2
Order By: Relevance
“…In 2017, the Greaney group described another double arylation reaction from diaryliodonium salt (Scheme ) . In their one‐pot reaction, the N‐heterocycle could undergo arylation with diaryliodonium salt to give an N‐aryl product, where the heterocycle can then act as a directing group for subsequent C−H arylation taking place in situ with the generated aryl iodide.…”
Section: Acyclic Diaryliodonium Saltsmentioning
confidence: 99%
“…In 2017, the Greaney group described another double arylation reaction from diaryliodonium salt (Scheme ) . In their one‐pot reaction, the N‐heterocycle could undergo arylation with diaryliodonium salt to give an N‐aryl product, where the heterocycle can then act as a directing group for subsequent C−H arylation taking place in situ with the generated aryl iodide.…”
Section: Acyclic Diaryliodonium Saltsmentioning
confidence: 99%
“…As ar esult, DMAP was inefficient and DBU gave am oderate yield of 51 %( entries 8a nd 9). Elevating the reaction temperature gave comparable yields of 2aa,w hereas the yields were significantly decreased at low temperatures (entries [10][11][12][13]. Further solvent screening, including DCM, toluene,D MF,T HF,D CE, and water, showed that DMF also afforded 2aa in 90 %y ield.…”
mentioning
confidence: 96%
“…[1] Interestingly,t he iodonium salts of E could undergo intramolecular aryl migration to generate ortho-iodo diaryl ethers under basic conditions without wasting the aryl residues (Scheme 1d). [12] Herein, we describe the detailed results.I tis worth mentioning that ortho-iodo diaryl ethers were sterically hindered and the C À Ib ond was fragile under the classical Ullman reaction conditions. [13] To begin our studies,w ec hose mesityl(2-((trifluoromethylsulfonyl)oxy)phenyl)iodonium tosylate (1a)asthe model substrate and the reaction was performed in the presence of 2.0 equivalents of ab ase,w ith acetonitrile as the solvent, at 25 8 8C( Table 1).…”
mentioning
confidence: 99%
“…[4] Among the commonly used transition-metal catalysts,r uthenium [5] offers an effective,e conomically attractive alternative to more costly palladium, platinum, or iridium catalysts, [6] often proceeding through mechanistically distinct pathways.T hus,p rotocols for the direct CÀH arylation under ruthenium catalysis have been developed, [7] with major contributions by Oi/Inoue, [8] Dixneuf, [9] and our group, [10] among others. [11] Despite the wealth of viable canonical, isohypsic arylations,s tudies on more challenging ruthenium-catalyzed dehydrogenative CÀH/CÀHa ctivation for the formation of CÀCbonds continue to be largely limited to the use of costly metal salts as terminal oxidants. [12] In contrast, exploiting the potential of mild aryl halides as oxidants through au nique manifold has been significantly hampered by scarce mechanistic insights.…”
mentioning
confidence: 99%